Current guidelines may not be the best for follow‐up of abnormal Pap smear results. Issue 7 (July 2018) - Burket, Jeffrey; Smith, Ashley; Arnold, Michael; Arthur, Benjamin; Bennett, Nick; Marshall, Bob
Abstract : PRACTICE CHANGER : Women aged 21 to 27 years with atypical squamous cells of undetermined significance (ASCUS) or low‐grade squamous intraepithelial lesions (LSIL) on Pap smear should have follow‐up with cytology at 6 months. For women aged 21 to 24 years, this tactic reveals more invasive cervical cancer than a 12‐month follow‐up, and for women 24 to 27 years old this strategy did not miss cervical cancer compared with going straight to colposcopy.1 Strength of recommendation: B, single, large, highquality retrospective cohort study Sundström K, Lu D, Elfström KM, Wang J, Andrae B, Dillner J, et al. Follow‐up of women with cervical cytological abnormalities showing atypical squamous cells of undetermined significance or low‐grade squamous intraepithelial lesion: a nationwide cohort study. Am J Obstet Gynecol. 2017; 216(1):48.e1–48.e15. CASE : A 24‐year‐old otherwise healthy woman recently underwent a Pap smear for routine cervical cancer screening. The results showed LSIL. She had a normal Pap smear 3 years ago and has completed a human papillomavirus (HPV) vaccination series. Should you follow current guidelines and do a repeat Pap smear in 12 months?